2008
DOI: 10.1158/1940-6207.capr-08-0125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mucin Depleted Foci in the Human Colon

Abstract: Aberrant crypt foci (ACF) originally described in rodents treated with colon-specific carcinogens have been identified also in humans at high risk of colon cancer (CRC) and are extensively used as cancer biomarkers. However, studies documenting the heterogeneity of ACF have questioned their precancerous nature. Recently, we described dysplastic foci depleted of mucins (MDF) in the colon of rats treated with colon-specific carcinogens. Like colon tumors, MDFs show activation of Wnt signaling driven by mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…3,6 Similarly, the number of MDF/colon in FAP is much higher than that in CRC. 7 We also showed that PIRC rat MDF have a high proliferative activity and a shift in the distribution of proliferating cells in the upper part of the MDF crypt, compared with the NM. Similar alterations in proliferation have been reported in dysplastic FAP polyps and in MDF present in carcinogentreated rats.…”
Section: Discussionsupporting
confidence: 53%
“…3,6 Similarly, the number of MDF/colon in FAP is much higher than that in CRC. 7 We also showed that PIRC rat MDF have a high proliferative activity and a shift in the distribution of proliferating cells in the upper part of the MDF crypt, compared with the NM. Similar alterations in proliferation have been reported in dysplastic FAP polyps and in MDF present in carcinogentreated rats.…”
Section: Discussionsupporting
confidence: 53%
“…Most human colon cancers have an Apc mutation, as do MDF in humans and rats (32). To unravel the mechanisms, we used a cellular model that represented the colorectal cancer stages that we investigated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Promotion was evidenced on a surrogate end point biomarker, mucin-depleted foci. MDF, formed by dysplastic crypts devoid of mucin, have been identified in the colon of humans at high risk for colon cancer (41). Like tumors, MDF harbor mutations in genes affecting colon carcinogenesis (Apc and K-ras) and show Wnt signaling activation (42), a dramatic reduction of MUC2 expression (43), and a strong activation of the inflammatory process (44), all features suggesting that MDF are precancerous.…”
Section: Discussionmentioning
confidence: 99%